Liberia Country Program Evaluation 2004-2011 : Evaluation of the World Bank Group Program - Independent Evaluation Group (Washington, DC: World Bank, 2013)
This report evaluates the outcomes of World Bank Group support to Liberia from its post-war reengagement in 2003 through 2011. The country has moved from total disarray to a solid foundation for inclusive development. Although development has not moved forward as quickly as hoped, substantial progress has been made. Public finance and key institutions have been rebuilt; crucial transport facilities have been restored; and hospitals, schools, and universities are operating. The debilitating burden of massive external debt has been eliminated. Although the government deserves most of the credit, this success would not have been possible without external development and security partners, including the World Bank Group. Regarding outcomes, the rebuilding of public institutions has seen substantial progress, with important achievements in restoring public finances and reforming the civil service. Regarding the rehabilitation of infrastructure, the World Bank Group has helped improve the conditions of roads, ports, power supply, and water and sanitation. However, World Bank Group financial support has been relatively modest with regard to facilitating growth, but it has helped with policy advice and in filling gaps left by other partners. With regard to the three cross-cutting themes of Bank Group strategy, some effective programs were carried out, including capacity development at several core public finance-related agencies. However, the integration of these themes across World Bank Group interventions, which was the underlying intent, still needs a vision and better articulated strategy. Finally, the Bank and the International Monetary Fund led efforts to reduce Liberia's inherited external debt burden under the enhanced Highly-Indebted Poor Country Initiative and the Multi-lateral Debt Relief Initiative mechanisms.